The Adult Dispositional Hope Scale (AHS) in Indonesian Population: Factorial Structure and Psychometric Properties - Riangga Novrianto; Adhityawarman Menaldi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The Adult Dispositional Hope Scale (AHS) is the first and primary measure that evaluates the hope construct. However, the instrument’s factorial structure is still debatable. The present study aims to validate and evaluate the factorial structure and psychometric properties of the Indonesian version of AHS. Participants were 221 Indonesian adults recruited via an online survey. Confirmatory Factor Analysis results showed that the two-factor model best represents the Indonesian version of AHS underlying factors (Δχ² (1) = 5.3774, p < 0.05). The Indonesian version of AHS also showed good validity and adequate internal consistency (???? = .791). Therefore, findings from this study suggest supporting evidence for the two-factor model of AHS and indicate that the Indonesian version of AHS is a valid and reliable instrument to measure hope construct in the Indonesian adult population.